Ticagrelor-associated ventricular pauses: a case report and literature review. Issue 1 (28th December 2018) - Low, Ashlea; Leong, Kai'En; Sharma, Anand; Oqueli, Ernesto
Abstract: Background: Ticagrelor is an oral anti-platelet agent that is a reversible and direct inhibitor of the adenosine diphosphate P2Y12 receptor. Ticagrelor's brady-arrhythmic potential was investigated in a sub-study of the PLATO trial, which concluded that the effects were transient and not clinically significant beyond the acute initiation phase. Since then, there have been emerging reports of ticagrelor-associated high-degree heart block, requiring drug discontinuation and pacemaker insertion. We present a case of symptomatic ventricular pauses in a patient loaded with ticagrelor post-percutaneous coronary intervention (PCI) for non-ST elevation acute coronary syndrome (NSTEACS) and review the literature relating to ticagrelor and its brady-arrhythmic potential. Case summary: A 59-year-old female presented to our hospital with NSTEACS and received an oral load of ticagrelor 180 mg following PCI to her mid-left circumflex coronary artery. Three hours after, four pauses were observed on telemetry over a 20 min period, the longest being 18.5 s in duration. Ticagrelor was ceased and clopidogrel commenced in place. No arrhythmic events were recorded on loop recorder interrogation following ticagrelor discontinuation. Discussion: The exact mechanism of ticagrelor-induced brady-arrhythmia is unclear, although inhibition of adenosine reuptake is proposed as likely due to structural similarities between ticagrelor and adenosine. In the setting of acute coronary syndrome treated with ticagrelor, extracellular adenosine concentrations are amplified by the ischaemic milieu with myocardial adenosine release and blunted cellular reuptake. This leads to enhanced agonism of adenosine A1 receptors, causing negative chronotropy and dromotropy. This case report highlights ticagrelor's brady-arrhythmic potential even in the absence of baseline conduction disease or concurrent confounding medications.